Model Pembelajaran Kurikulum Merdeka Belajar pada Bidang Studi PAI di SMA Abi Huroiroh Perak Jombang - Mochamad Mansur; Muhammad Khoirur Roziqin; Zaki Ahmad Fauzan (Lembaga Yasin AlSys, 2026)
The implementation of the Kurikulum Merdeka in pesantren-based schools faces challenges related to inadequate teacher preparedness and limited technological facilities, particularly the policy prohibiting students from using digital devices. This study aimed to analyze the implementation of the Kurikulum Merdeka learning models in Islamic Religious Education (PAI) at SMA Abi Huroiroh Perak Jombang and identify the challenges and solutions in their implementation. The study employed a qualitative approach with a descriptive design. Data were collected through observation, interviews, and documentation involving teachers, the vice principal for curriculum affairs, and students as research informants. The results showed that the Kurikulum Merdeka was implemented through Project-Based Learning (PjBL) and Problem-Based Learning (PBL). The implementation of both models supported improvements in student engagement, critical thinking skills, and the application of Islamic values in learning. The challenges identified included teachers’ limited ability to develop learning modules, time constraints, students’ adaptation to learning patterns, and inadequate interactive facilities. These challenges were addressed through teacher training and mentoring and by adapting the learning process to pesantren conditions. This study confirms that the implementation of PjBL and PBL can support improvements in the quality of Islamic Religious Education and the development of students’ Islamic character despite limited digital infrastructure. These findings provide practical implications for pesantren-based schools in flexibly adapting the Kurikulum Merdeka according to institutional characteristics, students’ needs, and the availability of learning facilities.